USE OF DIGITAL TECHNOLOGIES IN INCREASING INVESTMENT ATTRACTIVENESS OF REGIONS AND IMPROVING THEIR ASSESSMENT METHODS - Qodirova Dilafruz Olimovna; Sharofiddinov Nozimjon Oktam ogli; Ubaydullayeva Go‘zalxon Murodqosim qizi (Scholar Express Journals, 2023)
The article highlights the issues of increasing the investment attractivenveness of regions and improving their evaluation methodology.
Keywords: digital economy; technology; innovation; territories; investments